Influenza A and B Virus-Triggered Epithelial–Mesenchymal Transition Is Relevant to the Binding Ability of NA to Latent TGF-β - Yang, Wenxian; Bai, Xiaoyuan; Li, Heqiao; Li, Huizi; Fan, Wenhui; Zhang, He; Liu, Wenjun; Sun, Lei (Frontiers in Microbiology, 2022)
Epithelial-mesenchymal transition (EMT) is an important mechanism of lung tissue repair after injury, but excessive EMT may lead to pulmonary fibrosis, respiratory failure, and even death. The EMT triggered by influenza A virus (IAV) and influenza B virus (IBV) is not well understood. We hypothesized that there was difference in EMT induced by different influenza virus strain. Here we discovered that both IAV (A/WSN/1933 (H1N1), WSN) and IBV (B/Yamagata/16/88, Yamagata) infection caused EMT in mouse lung and A549 cells, and more EMT-related genes were detected in mice and cells infected with WSN than those infected with Yamagata. Neuraminidase (NA) of IAV is able to activate latent TGF-β and the downstream TGF-β signaling pathway, which play a vital role in EMT. We observed that IAV (WSN) triggered more activated TGF-β expression and stronger TGF-β/smad2 signaling pathway than IBV (Yamagata). Most importantly, WSN NA combined more latent TGF-β than Yamagata NA in A549 cells. Collectively, these data demonstrate that both IAV and IBV induce TGF-β/smad2 signaling pathway to promote EMT, which might depend on the binding ability of NA to latent TGF-β.